The Magic of the Personal Touch: Field Experimental Evidence on Money and Appreciation as Gifts - Christiane Bradler; Susanne Neckermann (Tinbergen Institute, 2016)
This paper makes use of two field experiments to explore individual effort responses to gifts. We extend the literature by looking at nonfinancial gifts and gifts that combine financial and nonfinancial elements with or without adding a ``personal touch.'' We find that non-pecuniary gifts that signal worker appreciation induce reciprocity. Most importantly, we find that there are interaction effects between money and appreciation. While money and appreciation are individually effective, they only work well together when they are combined with a personal touch. This points to the importance of interpersonal elements in gift giving and has important implications for how to effectively elicit worker effort.
Keywords: C93; M52; 330; gift exchange; reciprocity; personnel economics; gratitude; personal touch; field experiment